Some Properties And Applications Of Rolled Zinc Strip And Drawn Zinc Rod - C. H. Mathewson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1919)
THIS paper was prepared upon request as a contribution to a symposium covering the manufacture, properties, and uses of the important non-ferrous metals. In approaching a subject as broad as this, there is a natural desire to build up a comprehensive and finished production which shall constitute a dependable source of information on all questions properly belonging to this branch of metal technology. There are, however, a number of circumstances, apart from the mere routine of labor and thought involved, which operate rather effectively against the possibility of completing such an ambitious program at the present time. First of all, as far as any public record of results is concerned, the commercial rolling, drawing, and forming of zinc with relation to changes of structure and properties-and this we consider to constitute the elements of metal technology-might as well be an unpractised art. We have never seen a published photomicrograph showing the structural characteristics of either hard or soft sheet or strip, although the structure of castings has been frequently described, and other coarse-grained structures resulting from hard-hammering and annealing have been reproduced. Thus, an author in this field must proceed to his task without much assistance from the literature, and the outcome can represent only a personal estimate of principles, facts, or findings, and not a summary